Social Representations of Sexuality in a Shared by Elderly Asylum of Rio Grande do Sul - Santos Braga, Paulo Cesar dos; Gaglietti, Mauro (Revista de Psicologia da IMED, 2013)
Human aging is a subject that has become present in many scientific areas nowadays. In psychology, it hasn’t been different. In this way, it was realized a qualitative research, inside one asylum in Passo Fundo, in Rio Grande do Sul, in 2011, looking for data’s about the social representation of sexuality, which was used a semi-structured interview with the elderly and with the place workers. Also, it was done a succinct literature review, presenting the participant  population  and the research place. This subject doesn’t matter only to academics, as well as society and especially the state, because the aging population is a reality in Brazil and in the world. This reality demand new behavior from all. We tried to answer the question, if social representation of sexuality on elderly may or may not provides support for the humanization of asylums and for the socialization of the elderly?